Persuasive Language Strategies in Instagram Influencer Content: A Pragmatic Analysis - Dewi Wulandari; Rahmah Fithriani; Pardi Pardi (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2026)
ABSTRACT This study aims to analyze persuasive language strategies used by influencers on Instagram from a pragmatic perspective. This research employs a qualitative descriptive design with data consisting of captions, comments, and audiovisual content containing persuasive elements. Data were collected through non-participant observation and documentation, and analyzed using an interactive model including data reduction, data display, and conclusion drawing. The findings reveal that influencers utilize various persuasive language strategies, such as directive, expressive, and assertive speech acts, as well as implicatures and credibility construction. Directive speech acts are used to encourage immediate action, while expressive acts and emotional appeals function to build a connection with the audience. In addition, implicature serves as an indirect persuasive strategy that enhances trust and authenticity. The results indicate that language in influencer content is not merely informative but also strategic in shaping audience perception, building trust, and influencing behavior. Therefore, a pragmatic approach provides deeper insights into how meaning and persuasion are constructed in digital communication. Keywords: Persuasive Language; Pragmatics; Instagram Influencers; Speech Acts; Digital Communication